BdcSP10 is a prophenoloxidase-activating protease in Bactrocera dorsalis. (January 2023) - Li, Wei; Dou, Wei; Wang, Jin-Jun
Abstract: Insects rely on a powerful and efficient innate immune system against microbial invaders. One of the most important immune processes is the melanization reaction, in which eumelanin is synthesized and deposited on the physically injured site or the surface of invading pathogens. The melanization reaction is mediated by prophenoloxidase (PPO), which is synthesized as an inactive zymogen and requires proteolytic activation through a clip serine protease cascade. This cascade has been characterized in several Lepidoptera insect species, but it is less understood in most Diptera insects. Here, with the means of reverse genetics and biochemistry, we characterized the function of a clip serine protease BdcSP10 from the oriental fruit fly Bactrocera dorsalis (Hendel), a significant agriculture pest to a broad variety of fruit and vegetable crops. BdcSP10 knockdown inhibited the melanization reaction and rendered adult flies more vulnerable to pathogenic infections. In addition, purified and activated BdcSP10 proteases promoted the melanization reaction in larval hemolymph and directly cleaved and activated purified PPO1 and PPO2 in vitro . Taken together, we identified BdcSP10 as a PPO-activating protease and validated its important role in the defense against microbial infection in B. dorsalis. This work broadens the understanding of the activation mechanism of the melanization reaction in Diptera insects. Graphical abstract: Image 1 Highlights: BdcSP10 is an immune-responsive gene; its expression increased significantly upon microbial challenge. Knock-down of BdcSP10 decreased PO activity of adult flies and rendered them more sensitive to microbial infection. Purified recombinant BdcSP10 could stimulate melanization in larval hemolymph. BdcSP10 could cleave and activate three recombinant PPOs (PPO1a/PPO2/PPO3) in vitro.